Study guides

☆☆

Q: How do you factor x2 plus 4x -96?

Write your answer...

Submit

Related questions

x2 + 4x - 96 = (x - 8)(x + 12).

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

x2+4x-32 = (x-4)(x+8) when factored

x2 + 4x + 6 can not be factored. If you want, you can reduce it to an expression with a single x term by comleting the square: x2 + 4x + 6 = x2 + 4x + 4 + 2 = (x + 2)2 + 2

(x-1)(x-3)

(6 - x)(2 + x)

(x+4) (x+6)

x2 + 4x - 60 factors into (x + 10)(x - 6). You can use the FOIL method to check your answers when you factor.

x+5 is a factor of x2+4x-5 use synthetic division to learn that the other factor is x-1

(x + 10)(x - 6)

y = x2 - 4x + 4 can be factored into y = (x-2)(x-2) The repeated factor is 2.

x2 - 4

x2 + 4x + 4 = (x+2)2

You can work this out with long division, by checking to see if (x2 - 1) is a factor of (2x4 + 4x3 - x2 + 4x - 3). It is. Unfortunately, the WikiAnswers system is somewhat limited in depicting things such as long division, so we won't be able to represent it here. In short though, (2x4 + 4x3 - x2 + 4x - 3) / (x2 + 1) is equal to 2x2 + 4x - 3. which means that: (x2 + 1) / (2x4 + 4x3 - x2 + 4x - 3) = (x2 + 1) / (x2 + 1)(2x2 + 4x - 3) = 1 / (2x2 + 4x - 3)

x2 - 4x - 32 = (x - 8)(x + 4)

x2 + 4x + 3 = (x + 1)(x + 3)

x2 + 4x + 3 =(x + 3) (x + 1)

x2-4x+4 = (x-2)(x-2) when factored

(x - 4) or (x + 8)

x2+4x+4 = 25 x2+4x+4-25 = 0 x2+4x-21 = 0 (x+7)(x-3) = 0 x = -7 or x = 3

x2 + 4x - 32 = (x + 8)*(x - 4)

X2 + 4X - 5 = 0 what two factor of - 5 add up to 4? (X - 1)(X + 5) ----------------- ( so, X = 1 and X = - 5 )

X2 + 4xx(x + 4)=======

X2 + 4X + 4 Ask yourself, what factors of 4 add up to 4? (X + 2)(X + 2) or, more commonly expressed as, (X + 2)2

4x(x2 - 2)